Sensory, chemical and microbiological changes during storage of jumbo squid mantle (Dosidicus gigas) at 0 and 5°C - Pariona-Velarde, Daniel (2022)
The aim of this study was to evaluate the sensory, chemical and microbiological changes in the mantle of giant squid (Dosidicus gigas) with skin (CP) and without skin (SP) stored on ice (0 ± 1 ºC) for 19 days and refrigerated (5 ± 1 ºC) for 8 days. Chemical evaluation was performed by analysing trimethylamine nitrogen (N-TMA), volatile base nitrogen (N-BVT), hypoxanthine/adenosine monophosphate ratio (Hx/AMP), pH, biogenic amines, and microbiological evaluation by the count of mesophilic, psychrophilic and enterobacteria bacteria. Sensory characteristics evaluated were odour (raw and cooked), flavour, texture, and general acceptability. Principal Component Analysis (PCA) and Pearson's Correlation (p<0.05) were used to find the association between sensory impairment and chemical or microbiological analyses. It is concluded that the analyses of Log(Put+Cad+Hist), Log (Psychrophiles) and Log. (mesophiles) would be adequate to describe the changes in the mantle of giant squid stored at 0 and 5 °C.